Pengelolaan Data Inventaris Barang Milik Daerah sebagai Upaya Meningkatkan Akurasi Administrasi Aset pada BKAD Kota Palangka Raya - Putra Yantenglim; Harjoni Harjoni; Delon Kurniawan; Yusuf Anwar (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the management of Regional Property (BMD) inventory data in improving the accuracy of asset administration at the Regional Finance and Assets Agency (BKAD) of Palangka Raya City. The research uses a descriptive qualitative approach with a type of field case study carried out through internship activities in the Asset Management Division of BKAD Palangka Raya City. Data collection was carried out through structured interviews, participatory observations, and documentation of the process of managing regional asset inventories. The results of the study show that regional asset management has been carried out through the use of digital information systems such as SIMDA-BMD, SIMBADA, and SIPD which support the process of recording, reconciliation, physical inventory, and reporting of Regional Property. However, inventory management still faces obstacles in the form of limited human resource competence, administrative inconsistencies between regional apparatus, incomplete asset legality, and suboptimal technology integration. Orderly and accurate management of inventory data has a positive impact on the transparency of asset administration, the quality of the preparation of regional financial statements, and supports the achievement of the Fair Opinion Without Exception (WTP) of the Financial Audit Board. This research contributes to strengthening accountable, effective, and digital-based regional asset governance in the local government environment.